2014
DOI: 10.7550/rmb.36352
|View full text |Cite
|
Sign up to set email alerts
|

Cold storage of the sperm of the endemic trout Oncorhynchus mykiss nelsoni: a strategy for short-term germplasm conservation of endemic species

Abstract: Aiming to determine an appropriate protocol for short-term storage of the sperm of San Pedro Mártir trout, Oncorhynchus mykiss nelsoni, wild fish previously matured in captivity were anesthetized and the semen, obtained by abdominal pressure, was suspended in Erdhal and Graham extender at 1:3, 1:6 and 1:9 dilution ratios and kept at 4° C for 9 days with an undiluted sample as control. The percentages of sperm motility and membrane integrity were assessed daily. The results indicated that sperm suspended at a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…Our results demonstrated that sperm functions are affected significantly by the age of the broodstock males and the time of cold storage, decreasing the sperm motility, viability, MMP, and increasing DNA frag and O2 level. These results are consistent with those obtained in previous investigations showing that short‐term storage of fish semen at low temperatures induces a significantly decrease of sperm functions, impairing motility, viability (Aguilar‐Juárez et al., ; Aramli et al., ; Şahin et al., ; Shaliutina, , ; Trigo et al., ), MMP (Trigo et al., ), increasing DNA frag (Pérez‐Cerezales et al., ; Shaliutina, , ;) and OS indices (Aramli et al., ; Shaliutina, , ). In the present study, our results of O2 level during cold storage provide new information in agreement with those reported by Shaliutina et al.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results demonstrated that sperm functions are affected significantly by the age of the broodstock males and the time of cold storage, decreasing the sperm motility, viability, MMP, and increasing DNA frag and O2 level. These results are consistent with those obtained in previous investigations showing that short‐term storage of fish semen at low temperatures induces a significantly decrease of sperm functions, impairing motility, viability (Aguilar‐Juárez et al., ; Aramli et al., ; Şahin et al., ; Shaliutina, , ; Trigo et al., ), MMP (Trigo et al., ), increasing DNA frag (Pérez‐Cerezales et al., ; Shaliutina, , ;) and OS indices (Aramli et al., ; Shaliutina, , ). In the present study, our results of O2 level during cold storage provide new information in agreement with those reported by Shaliutina et al.…”
Section: Discussionsupporting
confidence: 91%
“…Short‐term storage is the most common technique utilised in the Chilean salmon industry, and previous researches have shown that it induces a significant decrease in sperm function (Aguilar‐Juárez, Ruiz‐Campos, & Paniagua‐Chávez, ; Aramli, Kalbassi, Nazari, & Aramli, ; Hajirezaee et al., ; Pérez‐Cerezales et al., ; Şahin, Zeki, & Balta, ; Shaliutina, , ; Trigo et al., ). It is consensually recognised that only spermatozoa of good quality with concentration ≥12 × 10 9 spermatozoa/ml, spermatocrit between 10% and 20%, and motility, viability, MMP >80% and DNA frag < 10% (Figueroa et al., , ; Merino et al., ; Pérez‐Cerezales, Gutiérrez‐Adán, Martínez‐Páramo, Beirãoa, & Herráez, ; Trigo et al., ) can be used for assisted reproductive techniques (ART).…”
Section: Introductionmentioning
confidence: 99%
“…Free amino acids like methionine improve spermatozoa viability in rainbow trout (Lahnsteiner, ). Moreover, dilution ratios of 1:2, 1:3, 1:6, 1:9 and 1:50 have been usually used in previously studies, and the higher dilution rates have been found preferable for rainbow trout spermatozoa in parallel with the current study (Aguilar‐Juárez, Ruiz‐Campos, & Paniagua‐Chávez, ; He & Woods, ; Trigo et al, ).…”
Section: Discussionmentioning
confidence: 75%
“…Storage of refrigerated semen is a simple and inexpensive procedure (Shaliutina et al., ) that can facilitate the management and reproduction programmes in aquaculture and also represent a useful strategy for preservation of threatened or endangered fish (Aguilar‐Juárez et al., ). However, there is a significantly decrease on sperm function after short‐term storage of fish semen (Lahnsteiner et al, ; Vuthiphandchai et al, ; Aramli et al., ; Shaliutina et al., ; Aguilar‐Juárez et al., ; Trigo et al., ) mainly due to oxidative stress (Lahnsteiner et al., ; Aramli et al., ; Shaliutina et al., ). The imbalance between the production of reactive oxygen species (ROS) and a biological systems ability to readily detoxify the reactive intermediates or easily repair the resulting damage is known as oxidative stress (Agarwal et al., ).…”
Section: Introductionmentioning
confidence: 99%